Problem Based Learning Animation Videos in Third Grade Indonesian Language Lesson Content - Ibnu Sina; Anak Agung Gede Agung; I Made Tegeh (Universitas Pendidikan Ganesha, 2023)
The learning process implemented in schools tends to be teacher-centered, so students wait for explanations of material from the teacher. This condition results in students needing help answering various problems and issues encountered in the learning process. This research aims to create problem-based learning animation videos for Class III Indonesian language content. This research uses ADDIE development research. The subjects of this research consisted of 1 learning design expert, 1 learning media expert, 1 learning content expert, individual testing (3 students), and small groups (9 students). The data collection method was obtained using the test and questionnaire method—quantitative and qualitative data analysis techniques. The results of this research show the validity of the learning design expert with a score of 95%, the learning content expert with a score of 94.54%, the learning design expert with a score of 86.15%, the results of individual trials with a score of 88.66%, and the results of small group trials namely a score of 89%. The effectiveness of learning media can be seen from the t-test with the calculated t value of 17.247 and t table of 1.717. The conclusion is that there is a significant difference in student learning outcomes between before and after using problem-based learning animated video media. This research implies that teachers can use the media in teaching, making it easier for students to understand the lesson material.